Experimental study on application of gas metal arc welding based regulated metal deposition technique for low alloy steel. Issue 15 (18th November 2022) - Bandhu, Din; Vora, Jay J.; Das, Subhash; Thakur, Ashish; Kumari, Soni; Abhishek, Kumar; Sastry, M. Nagaphani
ABSTRACT: In this work, a modified and advanced welding technique named regulated metal deposition (RMD) has been implemented for joining ASTM A387-11-2 low alloy steel plates. Mechanical behavior and microstructure of welded joints have been experimentally investigated after the recommended heat-treatment process. The microstructures of welded joints were examined using optical and scanning electron microscopes. Optical microscopy indicated the existence of bainitic and martensitic phases in the base material and weld zone, respectively. Scanning electron microscopy combined with energy dispersive x-ray analysis displayed the presence of martensitic colonies as well as deposits of carbide precipitates in both weldments. The mechanical properties of these weldments, namely micro-hardness, tensile strength, and impact strength were also investigated. A comparative study has also been carried out for the same material using the conventional gas metal arc welding, in which the microstructure and mechanical behavior of regulated metal deposition weldments have been compared to those of gas metal arc weldments. Regulated metal deposition weldments showed better mechanical behavior than the gas metal arc weldments for low alloy steel.